Media edukasi berbasis android untuk meningkatkan pengetahuan tentang anemia pada remaja - Lulu Luthfiya; Aghitsna Fyrodhika; Kartika Pibriyanti; Fathimah Fathimah (MEDIA ILMU KESEHATAN, 2022)
Background: One of the common adolescent problems is anemia. Knowledge is one of the factors that influence of anemia. One of the media that increase knowledge is educational media based on android. educational media based on android is more interesting than the other media. Adolescent is the most group of internet and android users among the other age groups.Objective: This research aim to know the effectiviness educational media based on android. Methods: The research was conducted by Quasy experimental with control group post-test design method which consisted of 2 groups, namely the intervention group that was given intervention by educational media based on android which created by a mock up system and the control group was given vide . The sample was 110 each group with purposive sampling. the data was analyzed by Stata 13.1 with mann whitney test.Results: Based on the results of statistical tests, it is known that there is a difference between intervention and the control group (p value <0.05). the average score of knowledge in the intervention group was 83.15 and the control group was 77.1. Conclusion: Android-based educational media has effect to increase the knowledge of anemia in adolescents